Anti-inflammatory properties of mangosteen peel extract on the mice gingival inflammation healing process - Putri, Khairani; Darsono, Lusiana; Mandalas, Henry (Padjadjaran Journal of Dentistry, 2017)
Introduction: Mangosteen (Garcinia Mangostana L.) peel extract has widely used in the pharmaceutical field due to its anticancer, anti-inflammatory, antibacterial, and immunity boost properties. It had been proofed to be able to prevent and reduce the amount of plaque and cure gingivitis. This study was aimed to compare mangosteen peel extract at the concentration of 12.5 and 25% on the mouse gingival inflammation healing process. Methods: This study was a true experimental laboratory study. The subjects consisted of 28 mice divided into four groups, which were negative control (Aquadest) group; positive control (0.2% of Chlorhexidine) group; 12.5% Group of mangosteen peel extract group; and 25% respectively. Examination of the inflammatory healing process was observed every 2 hours during 6 hours, and the inflammatory measurements of mouse gingival performed by using calipers. Data obtained was analyzed with the one-way ANOVA test (α=0.05) and the Tukey’s range test. Results: The results from the one-way ANOVA test and the Tukey’s range test found that there was a significant difference on the inflammation size between the group with 12.5% of mangosteen peel extract and the group with aquadest and 0.2% of chlorhexidine. Meanwhile, the mice group with 12.5% of mangosteen peel extract and group with 25% of mangosteen peel extract did not show a significant difference in inflammatory size decrease. Conclusion: The mangosteen peel extract at the concentration of 12.5% was showing the highest anti-inflammatory potentials since the first measurement on the second hour after treatment.